The Role of Clove Farmer's Wife in Meeting Household Needs - Rika Malia Putri; Bahtiar; Dewi Anggraini (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
This study aims to discover the role and driving factors of the clove farmer's wife in meeting household needs in Patowonua Village, Lasusua District, North Kolaka Regency. The research approach used is descriptive qualitative, which is intended to describe reality in explanations and descriptive narratives. Data obtained through interview and observation techniques in the Patowonua Village community. The results of this study indicate that the role of the wife of a clove farmer in meeting household needs is helping the husband grow crops; managing household finances; sell the results of farming; borrow money from family; participate in producing agricultural commodities. The participation of clove farmer's wives in meeting household needs is driven by several factors, namely the desire to increase family income; to fill in spare time; and there is an encouragement of interest to help her husband.